Multicenter clinical experience with recombinant soluble thrombomodulin for disseminated intravascular coagulation associated with severe acute cholecystitis. Issue 176 (April 2019) - Ogura, Takeshi; Eguchi, Takaaki; Amano, Mio; Sano, Tatushi; Nishioka, Nobu; Miyano, Akira; Tsujimae, Masahiro; Tanimura, Hirohisa; Yamada, Tadahiro; Terashima, Yoshihiko; Okada, Akihiko; Higuchi, Kazuhide
Abstract: Background: Severe acute cholecystitis (AC) is defined by the association of organ dysfunction, including hematological dysfunction, with AC. Severe AC is often complicated by disseminated intravascular coagulation (DIC), the diagnostic criteria of which overlap with AC-associated hematological dysfunction. Since the diagnosis of DIC often delays definitive surgical management of severe AC, treatment of DIC in this setting is clinically important. Recombinant human soluble thrombomodulin (rTM) is a new agent that has proven clinically useful for treating DIC. However, the relevance of rTM to sepsis-induced DIC caused by AC has not been clinically evaluated. This retrospective multicenter study aimed to determine the clinical impact of rTM on sepsis-induced DIC caused by AC. Methods: This retrospective multicenter study initially included 68 consecutive patients and proceeded between July 2014 and December 2017. The inclusion criterion was sepsis-induced DIC caused by severe AC due to benign disease. Sixteen of the 68 patients were excluded in this study due to having advanced malignant tumors. Finally, 42 patients were enrolled in this study. We treated DIC with AC using Recomodulin® Injection (rTM) at doses of 130 or 380 U/kg/day. Results: 17 and 25 patients were treated with and without rTM, respectively. Values on days 3 and 7 did not significantly differ between the groups for PT-INR (P = 0.38 and P = 0.16, respectively) and FDP (P = 0.06 and P = 0.08, respectively), and PLT was significantly increased in the rTM group at day 7 (P = 0.03). Resolution rates of DIC on day 7 were significantly higher in the group treated with, than without rTM (94.1% [16/17] vs. 68.0% [17/25], P = 0.04). Two patients in each group died of sepsis-induced DIC associated with severe AC, and thus mortality rates did not significantly differ. Conclusions: rTM can may be improve the resolution rate of sepsis-induced DIC due to severe AC. Future studies should include more patients to validate our findings. Highlights: Recombinant human soluble thrombomodulin (rTM) has been developed as a key drug for disseminated intravascular coagulation (DIC). This retrospective multicenter study aimed to determine the clinical impact of rTM on sepsis-induced DIC caused by severe acute cholecystitis. Resolution rates of DIC on day 7 were significantly higher in the group treated with, than without rTM (94.1% [16/17] vs. 68.0% [17/25], P=0.04). rTM appears to have clinical benefit for sepsis-induced DIC patients with severe acute cholecystitis.